Study of the phyto-diversity of Birendra Multiple Campus - Das, Manoj K.L. (BMC Journal of Scientific Research, 2020)
The present study was assess the vascular flora of the Birendra M. Campus, Chitwan, Nepal in various seasons. The campus area had many wild and cultivated plants which were disturbed by cattle grazing over exploitation and uses of herbicides. 115 plant species belonging to 51 families were reported from the campus premises. There were 66 species were cultivated and numbers of wild species were 49. There were 63 herbs 18 shrubs 23 trees and 8 climbers. 48 annual, 2 biennial and 65 perennial plants were reported.